2012
DOI: 10.1093/infdis/jis499
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Phases of Blood Gene Expression Pattern Through Tuberculosis Treatment Reflect Modulation of the Humoral Immune Response

Abstract: The fast initial down-regulation of expression of inflammatory mediators coincided with rapid killing of actively dividing bacilli, whereas slower delayed changes occurred as drugs acted on dormant bacilli and coincided with lung pathology resolution. Measurement of biosignatures during clinical trials of new drugs could be useful predictors of rapid bactericidal or sterilizing drug activity, and would expedite the licensing of new treatment regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
209
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 217 publications
(238 citation statements)
references
References 37 publications
23
209
1
2
Order By: Relevance
“…We identified remarkable similarity between the datasets, with overexpression of modules annotated with IFN, inflammation functions, monocyte and neutrophil functions, and underexpression of B-and T-cell modules. These findings are in keeping with the individual studies that have included grouped modular analysis [4,7]. Where grouped modular profiles were less consistent, this may have resulted from the small cohort sizes used and emphasises the need for individual studies to be appropriately powered to detect all differentially expressed genes.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…We identified remarkable similarity between the datasets, with overexpression of modules annotated with IFN, inflammation functions, monocyte and neutrophil functions, and underexpression of B-and T-cell modules. These findings are in keeping with the individual studies that have included grouped modular analysis [4,7]. Where grouped modular profiles were less consistent, this may have resulted from the small cohort sizes used and emphasises the need for individual studies to be appropriately powered to detect all differentially expressed genes.…”
supporting
confidence: 61%
“…Publicly available datasets that had active TB patients versus healthy controls, latently infected or patients post-treatment were identified and retained. The latter three cohorts are synonymous transcriptionally at the group level [4,6,7]. HIV-infected individuals were excluded from this analysis.…”
mentioning
confidence: 99%
“…These studies mostly relied on peripheral blood samples from patients with active ( pulmonary) TB disease directly after diagnosis and contrasted gene expression profiles to those of healthy (infected) controls or patients with other inflammatory/pulmonary disorders (Jacobsen et al 2007;Mistry et al 2007;Berry et al 2010;Maertzdorf et al 2011aMaertzdorf et al ,b, 2012Bloom et al 2013;Cliff et al 2013;Kaforou et al 2013). Each individual study performed extensive data analysis to identify key signatures that could discriminate TB disease from the respective control group(s).…”
Section: Transcriptomic Approaches To Tb Biomarker Discovery a Meta-lmentioning
confidence: 99%
“…The blood gene signature from the publically available data set in the NCBI-GEO (National Center for Biotechnology Information Gene Expression Omnibus) database, accession number GSE31348, was used to analyze PKC expression of all isoforms during TB treatment. 20 For human lung proteomics, we analyzed the available data that have been deposited into the PRIDE partner repository with the data set identifier PXD003646. The heat map plot was constructed by calculating z-scores of PKCd abundance in different types of granulomas derived from multidrug-resistant TB patients.…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed a publicly available data set from an independent study 20 that reported whole-blood expression profiles of 27 first-time TB patients before and after treatment. We found that PKCd was the most abundantly expressed isoform compared with other PKC isoforms.…”
Section: Increased Expression Of Pkcd During Active Tb Diseasementioning
confidence: 99%